Efforts to Improve Students' Understanding of Addition and Subtraction Operations through Demonstration Method in Mathematics Subject - Dewi, Pinta; Yani, Ahmad (Nashir Al-Kutub Indonesia, 2024)
This action research aimed to improve students' understanding of addition and subtraction operations through the demonstration method in Mathematics for Grade 1 students at SDN Tamansari 07 Pagi, West Jakarta. The initial assessment revealed challenges faced by students in comprehending these fundamental mathematical concepts. The study utilized a Classroom Action Research approach with 32 students as participants. Data collection methods included documentation studies, observations, field notes, and tests. The research process involved two cycles, each comprising planning, action implementation, observation, and reflection stages. The implementation of the demonstration method in teaching addition and subtraction operations led to significant improvements in students' comprehension levels. The study showed a progressive increase in students' average scores from pre-test to post-test in each cycle, indicating enhanced learning outcomes. Students exhibited increased enthusiasm, better differentiation of addition and subtraction operations, and improved concentration during the lessons. Based on the research findings, it is recommended that educators consider incorporating the demonstration method into their teaching practices to enhance students' understanding of mathematical concepts. Continuous professional development on innovative teaching strategies, such as demonstrations, can benefit both teachers and students in achieving better academic outcomes in Mathematics. Further research could explore the long-term effects of the demonstration method on students' mathematical proficiency and investigate its applicability across different grade levels.